Structured Oral Examinations in Internal Medicine - Case A - Hani Almoallim; Ali Alkatheeri; Alaa Monjed; Fozya Basheer; Abdullah Tawakol; Ahmad Imam; Abdulsalam Noorwali; Kamran Hameed (Association of American Medical Colleges, 2009)
Abstract Introduction This resource is a structured oral examination in internal medicine designed for sixth-year medical students. This resource is part of a series of nine cases published in MedEdPORTAL. In this case, a 55-year-old businessman presents to the emergency room with a 1-day history of chest pain. He has returned recently from a long business trip. He is tachycardic with signs of pleural effusion. Methods There is an introductory statement for the case which is given to the candidate at the beginning of the 30-minute exam time. The examiner will then ask the candidate to inquire about further relevant historical points. The candidate will be fed with the points that he/she requested and will be prompted to ask important questions that were missed. There are no patients or patient simulators required. The candidate will then be asked in a similar fashion to mention what physical findings will be expected to look for with this history. The exam will continue with requesting and interpreting investigations related to the case. The exam for each case will end by exploring the differential diagnosis and discussing with the candidate the general management principles for this case. Safety issues and professionalism are also addressed in the checklist provided for each case. Results A majority of our students enjoyed the exam from personal and written feedback we got after the exam. Discussion This approach of examination is very convenient to both students and examiners. It is structured and standardized. We were successfully able to avoid almost all disadvantages associated with the long case format.